Screening of anaerobes producing antimicrobial substances - Kirn, B.-H. (1996)
To develop new biologically active compounds produced by anaerobes, 677 soil samples were collected and used to isolate 1,889 anaerobic bacteria. Among the isolates 427 strains were strict anaerobes and the remaining 1,462 strains were facultative anaerobes. From 427 strictly anaerobic isolates, 88 strains showed antibacterial activities, and 21 strains were selected for the further studies.